Effects of Apilarnil on Type 2 Diabetes-Induced IRS-1/PI3K/Akt Mediated Insulin Resistance in Male Rats - Karagözoğlu, Fatma; Şahin, Emre; Melek, Şule; Bediz Şahin, Saliha; Koca, Recep Hakkı; Yüksel, Hayati; Güngören, Alper (American Chemical Society (ACS), 2025)
Diabetes is one of the most important chronic and metabolic health problems seen as an epidemic of the 21st century. The incidence of diabetes is gradually increasing, and different methods are used to treat it. Apitherapy products such as honey, propolis, royal jelly, and bee venom can be used as an alternative to treat diabetes and reduce symptoms. One of these apitherapy products is Apilarnil, which has not yet become popular. The hypolipidemic, hepatoprotective, androgenic, anabolic, and immune system enhancing properties of Apilarnil indicate that it may be effective in the treatment of type 2 diabetes or in reducing the symptoms. The study aimed to determine the therapeutic effect of Apilarnil on insulin resistance and the possible underlying mechanism. In the study, 40 8 week-old male Wistar albino rats were used. The rats were divided into 5 groups as Control, Diabetes, Diabetes + Api1 (125 mg/kg/day lyophilized Apilarnil), Diabetes + Api2 (250 mg/kg/day lyophilized Apilarnil) and Diabetes + Api3 (500 mg/kg/day lyophilized Apilarnil). Each group consisted of 8 rats. Apilarnil doses were administered by oral gavage with 1 mL of distilled water, 5 days in a week, during the last 6 weeks. The levels of Nrf2, NF-κB, TNF-α, total IRS-1, p-IRS-1, PI3K p85, total Akt, p-Akt, IL-1B, and GLUT4 proteins were determined in target tissues by Western blotting. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol (TC), and triglyceride (TG) levels were detected in the serum. Serum superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), malondialdehyde (MDA), and insulin levels were determined by the ELISA method. According to the data obtained in the study, the application of Apilarnil, compared to the diabetes group, balanced some findings, but did not demonstrate a fully antidiabetic effect.
Keywords: Chemistry; QD1-999; Article